Pengaruh Teknologi Informasi dan Komunikasi Dalam Pengembangan Potensi Daerah dan Keberlangsungan UMKM - A. St. Fatmawaty; A. Muhammad Arif Bijaksana; Rafilus Sampe; Muhammad Nasrun; Luciana Buarlele; Ade Sugiarti (JOURNAL OF TRAINING AND COMMUNITY SERVICE ADPERTISI (JTCSA), 2024)
This study aims to determine how the influence of Information Communication Technology in the development of regional potential and the sustainability of MSMEs in Padoang-Doangan Village. The data used in the study is a type of Quantitative data, where the data is obtained from the results of distributing questionnaires to respondents related to the problem being studied. Observation and distribution of questionnaires were carried out with the aim of collecting data. The results of research and data analysis using statistical calculations with SPPS (Statistical Package for the Social Science), the significance value of X on Y1 is 0.006 where 0.006 <0.05 while the tcount value is obtained at - 3.026 < ttable value 2.060. While X on Y2 is 0.00 < 0.05 where the tcount is -22.385 < ttable 2.060. So the author draws the conclusion that ICT has no effect on the development of regional potential and the sustainability of MSMEs in Padoang-Doangan Village, Pangkep Regency.